Muco‐Penetrating Lipid Nanoparticles Having a Liquid Core for Enhanced Intranasal mRNA Delivery - Nipuni Maniyamgama; Ki Hyun Bae; Zi Wei Chang; Jialing Lee; Melgious J. Y. Ang; Yong Jie Tan; Lisa F. P. Ng; Laurent Renia; Kevin P. White; Yi Yan Yang (Advanced Science)
Abstract Intranasal delivery of mRNA vaccines offers promising opportunities to combat airborne viruses like SARS‐CoV‐2 by provoking mucosal immunity, which not only defends against respiratory infection but also prevents contagious transmission. However, the development of nasal mRNA vaccines has been hampered by the lack of effective means to overcome the mucus barrier. Herein, ionizable lipid‐incorporated liquid lipid nanoparticles (iLLNs) capable of delivering mRNA cargo across airway mucosa are designed. Adjusting the ratios of ionizable and cationic lipids allows fine‐tuning of the pKa of iLLNs to the range of nasal mucosal pH (5.5–6.5), thus facilitating mucus penetration via the formation of near‐neutral, PEGylated muco‐inert surfaces. When nasally administered to mice, the top candidate iLLN‐2/mRNA complexes enable about 60‐fold greater reporter gene expression in the nasal cavity, compared to the benchmark mRNA‐lipid nanoparticles (ALC‐LNP) having the same lipid composition as that of BNT162b2 vaccine. Moreover, a prime‐boost intranasal immunization of iLLN‐2/mRNA complexes elicits a greater magnitude of SARS‐CoV‐2 spike‐specific mucosal IgA and IgG response than ALC‐LNP, without triggering any noticeable inflammatory reactions. Taken together, these results provide useful insights for the design of nasally deliverable mRNA formulations for prophylactic applications.